2016
DOI: 10.1210/jc.2015-1988
|View full text |Cite
|
Sign up to set email alerts
|

PROK1 Level in the Follicular Microenvironment: A New Noninvasive Predictive Biomarker of Embryo Implantation

Abstract: PROK1 levels in FF and FCM could constitute new predictive noninvasive markers of successful embryo implantation in conventional in vitro fertilization-embryo transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…The signaling pathways include, cAMP, Akt, and p42-p44 MAP-kinases phosphorylation and calcium mobilization. PROKs regulate a stunning array of biological functions such as gastrointestinal motility (LeCouter et al, 2001;Lin et al, 2002), circadian rhythm regulation, neurogenesis, angiogenesis, pain perception, mood regulation, and reproduction (Brouillet et al, 2010(Brouillet et al, , 2012bAlfaidy et al, 2016;Zhao et al, 2019). Dysregulation of PROKs/PROKRs signaling pathways have been reported in a variety of diseases, such as cancer, abnormal angiogenesis and pregnancy pathologies (Brouillet et al, 2010(Brouillet et al, , 2012bAlfaidy et al, 2016;Traboulsi et al, 2017;Zhao et al, 2019).…”
Section: Prokineticin Family In the Control Of Placental Angiogenesismentioning
confidence: 99%
“…The signaling pathways include, cAMP, Akt, and p42-p44 MAP-kinases phosphorylation and calcium mobilization. PROKs regulate a stunning array of biological functions such as gastrointestinal motility (LeCouter et al, 2001;Lin et al, 2002), circadian rhythm regulation, neurogenesis, angiogenesis, pain perception, mood regulation, and reproduction (Brouillet et al, 2010(Brouillet et al, , 2012bAlfaidy et al, 2016;Zhao et al, 2019). Dysregulation of PROKs/PROKRs signaling pathways have been reported in a variety of diseases, such as cancer, abnormal angiogenesis and pregnancy pathologies (Brouillet et al, 2010(Brouillet et al, , 2012bAlfaidy et al, 2016;Traboulsi et al, 2017;Zhao et al, 2019).…”
Section: Prokineticin Family In the Control Of Placental Angiogenesismentioning
confidence: 99%
“…Studies have indicated that PROK1 expression in human, chimpanzee and bovine ovaries exhibited clear spatial and temporal specificity ( 8 , 14 , 18 ). It has also been revealed that PROK1 is dynamically distributed during folliculogenesis, meaning that the expression of PROK1 in primordial and primary follicles is significantly higher compared with expression in the antral follicles ( 19 ). This suggests that the differential regulation of PROK1 expression by hormones exists during follicular maturation ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been revealed that PROK1 is dynamically distributed during folliculogenesis, meaning that the expression of PROK1 in primordial and primary follicles is significantly higher compared with expression in the antral follicles ( 19 ). This suggests that the differential regulation of PROK1 expression by hormones exists during follicular maturation ( 19 ). It has been revealed that human chorionic Gn (HCG) can increase PROK1 expression in luteinizing granulosa cells and the placenta by binding with luteinizing hormone/choriogonadotropin receptor ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous publication had shown that PROK1 inhibits and controls trophoblast invasion in human pregnancy [ 12 ], whereas a recent prospective study suggested PROK1 may facilitate an embryo endowing with adequate implantation potential [ 13 ]. Moreover, aberrant expression or activity of PROK1 and its receptors are also reported to be associated with several gestational complication, and most were related to inadequate or inappropriate trophoblast invasion, such as gestational trophoblastic diseases, recurrent pregnancy losses, preeclampsia, and intrauterine fetal growth restriction [ 11 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%